Assessing the Risk Factors of Violent and Non-violent Suicide Attempt Methods: A Population-based Cross-sectional Study - Amin Moradi; Ehsan Mosafarkhani; Fateme Nikbakht; Zahra Amiri; Ali Vafaee Najar (Iranian Journal of Medical Sciences)
Background: Suicide is a serious global public health issue. It is the fourth-leading cause of death among young people between the ages of 15 and 29. Therefore, the present study was conducted to determine the important risk factors associated with violent and non-violent methods of committing suicide.Methods: This research was a cross-sectional study that included all people who attempted suicide between 2019 and 2023 and were part of the population covered by Mashhad University of Medical Sciences (Mashhad, Iran). Predictive variables for suicide attempts included age, sex, education, marital status, occupation, place of residence, drug abuse, smoking, psychiatric diagnoses, and the intended outcome of violent and non-violent methods. Logistic regression analysis was used to model the relationship between selected risk factors and the response variable. The data were analyzed using STATA software version 14. P<0.05 was considered statistically significant.Results: Among the 18,281 people, 53% were men. Men, those who had lost their wives, people who lived in suburban areas, and people who had self-employed jobs or were unemployed, had higher rates of attempted suicide using violent methods. The chance of using violent methods was found to be 64% lower in women than in men (OR=0.36, 95%CI=0.30-0.43) and 45% higher in single individuals than in married people (OR=1.45, 95%CI=1.20-1.75).Conclusion: This study found that several factors influenced the choice of method for committing suicide. Men, those who had lost their wives, suburban inhabitants, those with insecure jobs or unemployment, and single people were more prone to use violent methods. Meanwhile, women, the elderly, and those with higher education levels showed a preference for non-violent methods.